Floristic Composition, Distribution, and Association of Pandanus (Pandanaceae) in Bukit Duabelas National Park Jambi - Dimas Prasaja (Biota, 2019)
Pandanus species is widely distributed over Bukit Duabelas National Park in Jambi. Suku Anak Dalam (SAD), a local community living in Bukit Duabelas National Park area, use the natural fibers from Pandanus for many necessities, such as plaiting, building materials, and performing mytological rituals. This study aimed to examine floristic composition, distribution patterns, and association of pandanus species in Bukit Duabelas National Park. Sampling was conducted using a striped line, with a plot of 35 sample plots. Dominance of species was calculated using dominant type of important Value Index (IVI) based on the density, frequency, and dominance of sample plot enumeration. Distribution patterns was analyzed using the Morisita Index, while association patterns were measured by Contingency tables and Chi-square tests. Floristic composition was mostly found in the seedling strata consisting of 106 species. The species with highest important value index (IVI=14.53) was Palaquium gutta. There were two species of Pandanus (Benstonea kurzii and Benstonea atrocarpa) were spread in groups and three species of pandanus (Pandanus labyrinthicus, Pandanus furcatus, and Pandanus immersus) were spread evenly. The pandanus species found was associated with Benstonea kurzii was Litsea sp1. This present study suggested that the conservation of pandanus species should be conducted as a piece of rehabilitation of tropical forests in Bukit Duabelas National Park.